PENYULUHAN PERLINDUNGAN KONSUMEN DAN ETIKA PROMOSI MEDIA SOSIAL BAGI PELAKU UMKM DESA - Rommy Hardyansah; Fayola Issalillah; Rafadi Khan Khayru; Rahayu Mardikaningsih; Mila Hariani; Didit Darmawan; Muhammad Yusron Maulana El-Yunusi (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Lekok District are now the primary target of a community service program focused on strengthening legal compliance and promotional ethics. This program specifically provides counseling on consumer protection laws and ethical digital marketing communication procedures. Business expansion through social media requires the application of the principles of information transparency, honesty, and product authenticity to safeguard consumer rights while building a trusted brand image, as stipulated in consumer protection regulations. This program utilizes several stages of methods, ranging from legal literacy education on the rights and obligations of business actors, legal risk assessments of misleading advertising practices, to direct guidance in formulating ethical promotional strategies. The final evaluation of the program showed an increase in business actors' awareness of their legal responsibilities for the goods and services they offer to the public. Through these efforts, it is hoped that the capacity of MSMEs in Lekok District will further increase, enabling them to have strong competitiveness based on legal compliance and order in business.